(untitled) (Palimpsesto, 2019)
This study examines some poems written by Elicura Chihuailaf in order to analyze the vision that mapuche people possess regarding their way of knowing, so as to understand the way these people have of conceiving nature and relating to it. With this in mind, this system of hermeneutic interpretation of Gadamer, as well as the bergsonian vision of ’intuition’ and the concept of ’being’ that Kusch set to refer to the natives worldview, have been applied.All of this has yielded as a result that the mapuche people know the world by means of contemplation, observation and interpretation of the language of nature, and the revelation through dreams. This implies that the way in which their knowledge is formed goes from inside to outside, which coincides with Bergson’s definition of ’intuition’ and Kusch’s thesis about man, nature and divinity triad, which gives meaning to the indigenous thought.